Safe transport for low-wage migrant workers in Singapore: discourses and political justifications - Idnani, Sonya Fairoze (Nanyang Technological University, 2024)
In recent years, there has been a proliferation of lorry-related road accidents involving low-wage migrant worker victims in Singapore. Yet, there has been a lack of political will to institute the banning of the use of lorries as work transportation for low-wage migrant workers. Using Critical Discourse Analysis to understand the perspectives and political justifications on this issue, this paper seeks to explore how parliamentary members, industry associations and migrant welfare groups strategically construct discourses to constitute and reconstitute the relations of low-wage migrant workers and risk acceptability. Additionally, this paper investigates which discourse the state co-opts and therefore legitimises in its formal exclusion of low-wage migrant workers from safe transport. This will be scrutinised against broader sociocultural codes of responsibility and economic peripherality to situate the discourses. The paper provides insight on how language is used as a means to legitimise and delegitimse legislation, seeking to demonstrate the lack of ‘neutrality’ in social policy and discourse construction on the issue of safe transportation for low-wage migrant workers.